2020
DOI: 10.1101/2020.08.10.244152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SDC3 acts as a timekeeper of myogenic differentiation by regulating the insulin/AKT/mTOR axis in muscle stem cell progeny

Abstract: Muscle stem cells (MuSCs) are indispensable for muscle regeneration. A multitude of extracellular stimuli affect MuSCs from quiescent progenitors to differentiated myocytes, the activity of which is modulated by coreceptors such as syndecan-3 (SDC3). Here we investigated the global landscape of SDC3-mediated regulation of myogenesis using a phosphoproteomics approach which revealed, with the precision level of individual phosphosites, the large-scale extent of SDC3-mediated regulation of MuSC signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…50 Upon myogenic differentiation, syndecan-3 reduces the activity of insulin receptor after interaction with AKT/mTOR pathway. 51 It was suggested that modulation of miR-143-3p and miR-100-5p via the mTOR pathway is involved in driving human MSC fate for tissue regeneration. 52 Both miRNAs act as mechanosensitive factors and their expression can be changed in response to matrix stiffness and RhoA activity.…”
Section: Mtor Pathway Role In Differentiation and Stemness Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…50 Upon myogenic differentiation, syndecan-3 reduces the activity of insulin receptor after interaction with AKT/mTOR pathway. 51 It was suggested that modulation of miR-143-3p and miR-100-5p via the mTOR pathway is involved in driving human MSC fate for tissue regeneration. 52 Both miRNAs act as mechanosensitive factors and their expression can be changed in response to matrix stiffness and RhoA activity.…”
Section: Mtor Pathway Role In Differentiation and Stemness Maintenancementioning
confidence: 99%
“…Upon myogenic differentiation, syndecan‐3 reduces the activity of insulin receptor after interaction with AKT/mTOR pathway. 51 It was suggested that modulation of miR‐143‐3p and miR‐100‐5p via the mTOR pathway is involved in driving human MSC fate for tissue regeneration. 52 Both miRNAs act as mechanosensitive factors and their expression can be changed in response to matrix stiffness and RhoA activity.…”
Section: Mtor Pathway Role In Differentiation and Stemness M...mentioning
confidence: 99%